2012
DOI: 10.1080/00140139.2012.672658
|View full text |Cite
|
Sign up to set email alerts
|

The influence of product aesthetics and usability over the course of time: a longitudinal field experiment

Abstract: A longitudinal field experiment was carried out over a period of two weeks to examine the influence of product aesthetics and inherent product usability. A 2 x 2 x 3 mixed design was used in the study, with product aesthetics (high / low) and usability (high / low) being manipulated as between-subjects variables and exposure time as a repeated-measures variable (3 levels). A sample of 60 mobile phone users was tested during a multiple-session usability test. A range of outcome variables was measured, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 42 publications
5
61
1
Order By: Relevance
“…It may be particularly useful when other information is absent and when quick decisions require frugal automatic, rather than effortful, processing (Hertwig et al, 2008;Marewski & Schooler, 2011). Research to date suggests that a range of other factors are likely to come into play when individuals interact with an interface over time when more considered and conscious decision-making takes place (see Hartmann et al, 2008;Sonderegger & Sauer, 2010;Sonderegger et al, 2012;Thielsch et al, 2013). Thielsch and colleagues (2013) suggest the elaboration likelihood model (Petty & Cacioppo, 1986;Petty & Briñol, 2012 in which choices are made on the basis of a combination of lowinvolvement processing (relying on cue-based heuristic processing) and high-involvement processing involving high cognitive processes and consideration of the strength of arguments for and against a particular choice.…”
Section: Discussionmentioning
confidence: 99%
“…It may be particularly useful when other information is absent and when quick decisions require frugal automatic, rather than effortful, processing (Hertwig et al, 2008;Marewski & Schooler, 2011). Research to date suggests that a range of other factors are likely to come into play when individuals interact with an interface over time when more considered and conscious decision-making takes place (see Hartmann et al, 2008;Sonderegger & Sauer, 2010;Sonderegger et al, 2012;Thielsch et al, 2013). Thielsch and colleagues (2013) suggest the elaboration likelihood model (Petty & Cacioppo, 1986;Petty & Briñol, 2012 in which choices are made on the basis of a combination of lowinvolvement processing (relying on cue-based heuristic processing) and high-involvement processing involving high cognitive processes and consideration of the strength of arguments for and against a particular choice.…”
Section: Discussionmentioning
confidence: 99%
“…While some findings supported Advances in Human-Computer Interaction 3 the "what is beautiful is usable" hypothesis [8,[14][15][16], others did not [10,17,18]. Remarkably, Ben-Bassat et al [14], Lee and Koubek [15], and Tuch et al [10] found perceived beauty to be affected by manipulated usability.…”
Section: Introductionmentioning
confidence: 61%
“…Second, in combination, both objective usability and aesthetic contribute to a positive perception of the overall appeal of a product and provide the user with the opportunity to express a desirable identity to others (HQI). Further research should take a longitudinal perspective on this issue and examine whether these effects also persist over time (see [17]). …”
Section: Practical and Theoreticalmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some studies also indicated that design aesthetics influence other outcome measures of usability tests such as user behavior and user emotions (c.f. [29,28]). Such findings indicate that in a usability test it is highly probable that the different outcome measures are severely biased by the aesthetical refinement of the product prototype.…”
Section: Aesthetics and The Usability Evaluation Of Smart Garmentsmentioning
confidence: 99%